2020
DOI: 10.2147/ott.s250850
|View full text |Cite
|
Sign up to set email alerts
|

<p>LEMD1-AS1 Suppresses Ovarian Cancer Progression Through Regulating miR-183-5p/TP53 Axis</p>

Abstract: Background/Aims: Long noncoding RNAs (lncRNAs) play a critical role in tumorigenesis and progression of ovarian cancer (OC). This study focused on the function and potential mechanism toward LEMD1-AS1 (LEMD1 antisense RNA 1) in the progression of ovarian cancer. Materials and Methods: The expression of LEMD1-AS1 in OC tissues was evaluated in TCGA and Gene Expression Omnibus datasets (GSE119056) and confirmed in OC cell lines via qRT-PCR (quantitative real-time polymerase chain reaction). Then, the location of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…[47][48][49] Additionally, some studies have focused on cancer pathways, which can be more complicated in clinical cases and lead to poor repeatability in clinical research. [50][51][52] In comparison, our study focused on RCC and TET1, which are more likely to be applicable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…[47][48][49] Additionally, some studies have focused on cancer pathways, which can be more complicated in clinical cases and lead to poor repeatability in clinical research. [50][51][52] In comparison, our study focused on RCC and TET1, which are more likely to be applicable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al. have demonstrated that LEMD1 antisense RNA 1 (LEMD1-AS1) can suppress OC progression and can be used as a biomarker to predict survival ( 96 ). HMGB proteins are closely related to DNA damage repair, among which HMGB3 is often overexpressed up to 20 times in cancer cells ( 97 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the increasing evidence, it could be considered that lncRNAs could not only serve as prognostic and predictive markers but also as highly specific therapeutic targets. As for the 14 HARlncRNAs, LEMD1-AS1 suppresses OC progression through sponging miR-183-5p and regulation of TP53 ( Guo and Qin, 2020 ). Moreover, the prognosis implication of LEMD1-AS1 has been demonstrated in OC in the previous study ( Zheng et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%